Work-related temporary hearing loss and associated factors among textile industry workers in Amhara region, Ethiopia: a cross-sectional study - Giziew Abere; Eshetu Abera Worede; Atalay Tadele Yirdaw; Azanaw Asega Belay; Beletu Kinfe (BMJ Open)
Objectives This study was designed to assess occupational noise exposure levels, prevalence of temporary hearing loss and associated factors among textile industry workers in Amhara region, Ethiopia.Design An institution-based, cross-sectional study was conducted between June and July 2022. Participants were selected via a simple random sampling technique.Setting Textile industry workers in Bahir Dar and Kombolcha.Participants A total of 413 study participants were included in the data analysis.Procedures and analysis The data were collected using a structured questionnaire. Area noise exposure levels in different work sections were measured using a sound level meter. Data analysis was done using Stata Version 14.0 software. Bivariate and multivariable logistic regression analysis were used to identify factors associated with temporary hearing loss. Adjusted OR with 95% CI and p-value<0.05 were used to determine statistical significance.Results A total of 413 workers participated in the study with a response rate of 97.9%. The age of respondents ranged from 22 to 59 years (median age 32 years). The prevalence of work-related temporary hearing loss was 38.7% (95% CI 34.14% to 43.6%). Weaving department (AOR=6.6, 95% CI 3.06 to 14.3) and higher sound pressure level (>90 dBA) (AOR=7.9; 95% CI 2.6 to 23.7) were significantly associated with work-related temporary hearing loss among textile workers.Conclusions The prevalence of work-related temporary hearing loss among textile industry workers was high. Weaving department and higher sound pressure level were significantly associated with work-related temporary hearing loss. Implementation of noise reduction measures, particularly in the weaving department, should be prioritised. Provision and enforcement of the use of hearing protection devices and establishment of regular hearing screening programmes to monitor workers' auditory health are advisable.